Pelatihan Pengenalan Tools Total Quality Management (TQM) pada PT. Arra Busana Muslim - Resi Juariah Susanto (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Industrial development has grown more rapidly, especially in the fashion or clothing business sector, in Indonesia itself, the majority of Muslims are Muslims, therefore the Muslim clothing industry is growing rapidly. This service aims to maintain quality in a company, namely PT. Arra Busana Muslim, where this business wants to develop, requires training on how to maintain sustainable Agas quality and fix existing problems using Total Quality Management so as to improve overall quality, from leaders to employees, as well as in terms of manufacturing production in order to reduce failures or losses in a production process.